Resultados de un estado de la cuestión sobre psicoterapia (2009)
ABSTRACT: The project of investigation State-of-the-art: Concept of Psychoterapy in Clinical Psychology is the result of a process that it initiated with the first passage of all methodology of investigation: The state of the question. The development of the work and the participation in the seed plot of the Group of Investigation PSYCONEX were the slips throughout - Psychology, Psychoanalysis and Connections, those that allowed to obtain a methodological clarity that goes beyond the theoretician and who consolidates exclusively during the practice, thus to obtain the obtaining of abilities in investigation. The State of the question circumscribed the problem and threw several questions, between which the following one was privileged: Which is the concept of psychoterapy in clinical psychology? Key words: Methodology of investigation, State of the question, Clinical Psychology, Psychoterapy.